Micro and macroscopic mechanical behaviors of high-density polyethylene under UV irradiation and temperature. (April 2020) - Hsueh, Hsiang-Chun; Kim, Jae Hyun; Orski, Sara; Fairbrother, Andrew; Jacobs, Deborah; Perry, Lakesha; Hunston, Donald; White, Christopher; Sung, Lipiin
Abstract: The macroscopic mechanical behavior of high-density polyethylene (HDPE) during photodegradation is characterized by decreases of tensile elongation-at-failure. An apparent linear relation between the elongation-at-failure and the molar mass indicates that the decrease of the elongation of HDPE over time is highly dependent on the decrease of the average molar mass. Possible preferential scission of the high molar mass chains was observed for HDPE exposed to ultraviolet (UV) irradiance higher than 40% (61 W/m 2 ) of the full intensity at 50 °C. Tensile modulus of HDPE exposed at 50 °C increased with the exposure time until reaching the complete loss of ductility except the 5% UV. For 40% UV/30 °C as well as for 5% UV/50 °C, the young modulus trend cannot be evaluated with performed (small) duration. Nanomechanical test results suggest that the increased tensile modulus is due to stiffening of the entire cross-section. Furthermore, HDPE showing the complete loss of ductility exhibited significantly higher modulus in the surface regions than the core regions particularly for the UV intensity higher than 40% (61 W/m 2 ), which increased crack sensitivity to cause embrittlement of the entire specimens. Highlights: Micro and macroscopic mechanical properties of high-density polyethylene were measured after accelerated weathering tests. Changes in mechanical properties of polyethylene depended on ultraviolet radiation and temperature levels. Both molar mass and internal stiffness of polyethylene contributed on loss of tensile ductility. Greater variations of internal stiffness in polyethylene were observed for the UV radiance higher than 61 W/m 2 .